Anisotropic growth and magnetic properties of nickel–zinc ferrite thin film by spin spray deposition. Issue 1 (1st January 2021) - Liu, Hai; Yu, Zhong; Fu, Bin; Ran, Maojun; Wu, Chuanjian; Jiang, Xiaona; Guo, Rongdi; Lan, Zhongwen; Sun, Ke
Abstract: NiZn ferrite thin films with different compositions were prepared by spin spray deposition on an enhanced ultrasonic system and significant improvements in microstructure and magnetic properties of spin-sprayed thin-films were observed and explained. The formation of triangular grain morphology as a result of anisotropic growth was discussed based on a thin-film growth mechanism, and the preferred (222) anisotropic growth was deduced as the consequence of a uniform, fast-rate deposition of high-quality ferrite thin film by spin spray. First-order reversal curve measurement was adopted to investigate the grain size distribution of the abnormal microstructure. Moreover, a transition of magnetization mechanism took place along the increment of iron concentration which resulted in a larger permeability at high frequency. These findings provide a valuable reference for an in-depth understanding of spin spray deposition and an effective way to tune the performance of ferrite thin-film material.